PENGAJARAN BAHASA INGGRIS BAGI STAF LINTAS DEPARTEMEN DALAM INTERKASI DENGAN TAMU DI LA TANO’S CANGGU - Ida Bagus Gde Nova Winarta; Putu Gede Budiartha; I Gusti Bagus Wahyu Nugraha Putra; I Komang Yoshika Putra Pratama (LOKATARA SARASWATI, 2026)
This community service activity is one form of student dedication to society through programs tailored to the needs of the community. The program was carried out La Tano’s Canggu, a guest house located in the tourism area of canggu, Bali. Based on the observations, it was found that cross department staff still experience limitations in communicating in English, especially when interacting with international guests. This condition may affect the quality of service and guest satisfaction. As an effort to solve this problem, students implemented a pratical English training program, focusing on daily communication according to the needs of each department. This program is expected to support the improvements of service quality at La Tano’s Canggu and provide long term benefits for the developments of the tourism sector in tha Canggu area.